Commercial and strategic relations departments Malaysia Petroleum Management Petronas KLCC / Nuralya Nabilah Mohamad Sapiny - Mohamad Sapiny, Nuralya Nabilah (University Technology MARA Sarawak, 2018)
In 1974, Petroliam Nasional Berhad or well known as PETRONAS was established as the fully integrated oil and gas multinational in Malaysia. Among the largest corporation on FORTUNE Global 500®, PETRONAS have been recognized as one of most the important organization or business in developing the national oil and gas resources which involved exploring, producing and delivering energy to meet the society’s needs. Thus, in ensuring the well movement of PETRONAS managing the exploration of oil and gas, PETRONAS have given a clearer focus on its upstream and downstream division. PETRONAS upstream comprises into five key portfolios and one of it is Malaysia Petroleum Management (MPM). In protecting and maximise a long-term value to PETRONAS as well as nation, Malaysia Petroleum Management is committed in managed Malaysia’s resources.